The big basic book of PCs - Bucki, Lisa A. (Prentice Hall , New Delhi, 1998)
"Illustrated lessons break complex tasks into simple steps. Pictures show you how your screen should look at each step. Text explains the details in non-technical terms you can understand." "Helpful examples and useful "projects" let you put your personal computer to work right away. Just follow the numbered steps for instant results. Learn how to set up and customize your personal computer so you can quickly be productive with Windows 95, the Internet, and many other applications." "101 fast answers solve your personal computer problems. A Quick Finder Table helps you locate your problem and its solution in no time."--Jacket
Keywords: Computer science